Comparison of KNN and Random Forest Algorithms on E-Commerce Service Chatbot - Zamakhsyari, Fardan; Makayasa, Bagas Adi; Hamami, R. Abudullah; Akbar, Muhammad Tulus; Cahyono, Andi; Amirullah, Amirullah; Hisyamuddin, Muhammad Zida; Siregar, Maria Ulfah (UIN Sunan Kalijaga Yogyakarta, 2025)
Technology has a profound influence on our lives, with the expansion of e-commerce being a significant outcome that warrants attention. Given the prevalence of smartphones equipped with messaging apps and fast networks, people often utilize these platforms to communicate with sellers, offering a convenient way for sellers to engage efficiently with a diverse customer base. Recognizing this trend, there is a need for digital transformation of services to improve operational efficiency. Thus, this study aimed to compare the efficiency of classification algorithms in e-commerce service chatbots. The researcher employed machine learning techniques, specifically KNN and Random Forest algorithms, in this case. To assess the feasibility of the application, the chatbot results will be tested using the confusion matrix method to determine accuracy. From this study, it was found that the KNN method, combined with calculating word weight using TF-IDF, produces an accuracy value of 71.4%, thus confirming its feasibility.